Sistem Informasi Kasir Toko Kembar menggunakan Framework Webix dan MongoDB - Kamaz, Randy Petra; Beeh, Yos Richard (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Toko Kembar is a store providing various daily necessities. The sales transactions at Toko Kembar are still conducted manually, despite the high number of transactions. Store staff must manually check item prices on records, calculate totals, and write purchase receipts. This process is time-consuming, often leading to long queues of buyers. Stock and transaction history records are also manually documented in books, making them susceptible to loss or damage. This research aims to design and develop a web-based cashier application to address these issues. The research method employed is Research and Development (R&D). This study produced a cashier application with transaction menu, transaction history menu, and item data menu features. Testing results indicate that the application effectively simplifies the transaction process and data management at Toko Kembar.